Fouiller sur l’estran : des contraintes et des opportunités - Cyrille Billard; Vincent Bernard; Marie-Yvane Daire; Frédérique Eynaud; Henri Gandois; Anthony Lefort; Elías López-Romero; Pierre Stéphan; Florence Verdin (Les Nouvelles de l’Archéologie, 2019)
On the seashore, archaeologi’cal remains appear well preserved and sometimes immediatly visible during erosion periods. But the constraints are accumulating at all levels : limited intervention time, water, movement of tides, rapid change due to erosion, access conditions to excavations, difficulty encountered in implementation of heavy infrastructures. For these reasons, the interventions on this area have been limited for a long time to simple observations acompanied by samples. The rise of seashore issues and the increasing coastal erosion lead to real survey or excavation projects. Carried out nor in terrestrial conditions, nor in underwater conditions, these operations required an original methodology, new tools or sampling methods.Some examples choosen in various contexts illustrate the reactivity and the adaptations needed in the study of sites generally well preserved, supplying frequently organic remains, even fish or crustacean remains.